The extent to which teachers at a full service school in Soweto understand and practice the principles of a full service school - Mokala, Ntsoaki Teresa (My University, 2017)
In South Africa, Full Service Schools were introduced in order to provide quality education to all learners to meet a full range of learning needs. These schools strive to address the barriers to learning and increase participation of learners and teachers in the teaching and learning process. For that matter, they enhance the flexibility of teaching and learning methods. In order to explore the extent to which teachers in a Full Service School understand and practice the principles of a Full Service Schools, this study focused on the practices of three educators. Direct observations, interviews and document analysis were used to collect data. The study made use of Florian’s framework of inclusive pedagogy and within this framework, teachers’ pedagogic practices were compared. The results showed that teachers understood the concept of inclusion, made use of different teaching methods and they further indicated that there are quite a number of challenges teachers face on a daily basis. Key words: inclusive education, inclusive pedagogy, inclusive practice, Full Service School
A research report submitted in partial fulfilment of the requirements for the degree of Masters of Education in faulty of Humanities at the University of the Witwatersrand Johannesburg. October 2017.